REFLECTIVE TEACHING AS ALTERNATIVE ASSESSMENT IN TEACHER EDUCATION: A CASE STUDY OF PRE-SERVICE TEACHERS - Gusti Astika (TEFLIN Journal: A publication on the teaching and learning of English, 2014)
Â Critical reflective teaching has been a goal of English teacher preparation program. Although many English educators have promoted and carried out reflective teaching in their methodology courses, success of such practice has been limited, not sufficiently reflecting what has been desired. Questions have been raised whether reflective teaching within pre-service English teacher education is a realistic aim. One argument for this has been: reflective teaching can only be learned by beginning teachers working in schools with experienced teachers who value critical reflection. This article examines 40 journals of teaching reflection produced by 40 pre-service English teachers after they completed teaching practicum in schools over a period of three months. The journals were analyzed using a theoretical model developed by Smith (2011) which encompasses different purposes with different forms of reflection: personal, interpersonal, contextual, and critical. The analysis shows that the teaching journals contained more reflection on the personal and contextual domains of teaching, indicating that the pre-service teachers were more concerned with the contextual aspects of teaching which influenced their practices in the classroom. It is recommended that a more balanced reflection be created as an alternative form of assessment in English teacher education involving personal as well as social aspects of teaching.Â